Dyadic interactions and scientific explanation - Boissonnade, Romain (My University, 2011)
The data that will be presented are part of a larger study in which 10-year-old children are observed elaborating scientific ideas about a physical phenomenon: buoyancy. They are presented with successive experimental activities during which, alone or with a peer, they regularly have to confront their predictions with the observation of whether different objects sink or not, and to try to build scientific explanations. Two activities will be considered here: sharing ideas in a dialogue and writing a general scientific explanation. These activities occur in a concrete context (available objects and tools) that constraints further elaborations. We would like to see to what extent these activities lead to different argumentative processes and conducts.
, XI Amsterdam-Lugano Colloquium on Argumentation Theory, Lugano, Suisse
Keywords: argumentation conception explanation physics